Implementation of the Kurikulum Merdeka in the Informatics subject at SMKN 1 Cimahi - Alvin Al Hafidz Wibowo (Hipkin Journal of Educational Research, 2026)
Informatics has become a crucial component of vocational education, particularly amid the digital transformation and the demand for 21st-century skills. The Kurikulum Merdeka, as an educational reform in Indonesia, offers flexibility and contextualization in curriculum design, making its implementation in vocational schools a relevant topic. This study aims to describe the implementation of Informatics at SMKN 1 Cimahi within the Kurikulum Merdeka framework. This research was conducted in response to the need for curriculum practices aligned with national education standards and industry demands. The approach used was a descriptive, qualitative one, based on observations and interviews with the school's curriculum coordinator. The results show that Informatics is contextually designed through In-House Training (IHT) activities and collaboration between department teachers, thus aligning with industry needs and the characteristics of vocational students. The learning strategies implemented are varied and adaptive, including the use of a Learning Management System (LMS) and a project-based approach to develop 21st-century competencies. Evaluation is carried out continuously through a combination of formative, summative, and project-based assessments. The main implementation challenges were infrastructure and software licensing limitations, which were addressed through a laboratory rotation strategy and the use of alternative software. This study contributes to the development of vocational-based Informatics subject practices that are relevant to the workplace.   Abstrak Mata pelajaran Informatika telah menjadi komponen penting dalam pendidikan vokasi, terutama di tengah transformasi digital dan tuntutan keterampilan abad ke-21. Kurikulum Merdeka sebagai bentuk reformasi pendidikan di Indonesia memberikan fleksibilitas dan kontekstualisasi dalam perancangan kurikulum, sehingga implementasinya di sekolah kejuruan menjadi kajian yang relevan. Penelitian ini bertujuan untuk mendeskripsikan implementasi mata pelajaran Informatika di SMKN 1 Cimahi dalam kerangka Kurikulum Merdeka. Penelitian ini dilakukan sebagai respons terhadap kebutuhan akan praktik kurikulum yang selaras dengan standar pendidikan nasional serta tuntutan industri. Pendekatan yang digunakan adalah deskriptif kualitatif melalui observasi dan wawancara dengan koordinator kurikulum di sekolah. Hasil penelitian menunjukkan bahwa mata pelajaran Informatika dirancang secara kontekstual melalui kegiatan In-House Training (IHT) dan kolaborasi antar guru jurusan, sehingga selaras dengan kebutuhan industri dan karakteristik murid vokasi. Strategi pembelajaran yang diterapkan bersifat variatif dan adaptif, termasuk penggunaan Learning Management System (LMS) serta pendekatan berbasis proyek untuk mengembangkan kompetensi abad ke-21. Evaluasi dilakukan secara berkelanjutan melalui kombinasi asesmen formatif, sumatif, dan berbasis proyek. Tantangan utama dalam implementasi adalah keterbatasan infrastruktur dan lisensi perangkat lunak, yang diatasi melalui strategi rotasi laboratorium dan penggunaan perangkat lunak alternatif. Studi ini berkontribusi pada pengembangan praktik mata pelajaran Informatika berbasis vokasi yang relevan dengan dunia kerja. Kata Kunci: Kurikulum Merdeka; mata pelajaran Informatika; pembelajaran berbasis proyek; strategi pembelajaran